2014
DOI: 10.1088/0957-0233/25/9/094010
|View full text |Cite
|
Sign up to set email alerts
|

Study of a vibrating fiber probing system for 3-D micro-structures: performance improvement

Abstract: This paper presents a system for measuring 3D micro-structures that uses an optical fiber probe equipped with a piezo element that causes the probe to vibrate. The optical fiber probe consists of a stylus shaft with a diameter of 3 µm and a glass ball with a diameter of 5 µm attached to the tip. The stylus is vibrated in a circular motion in a single plane. The vibrator mechanism is introduced to prevent adhesion of the stylus tip to the surface being measured. This adhesion, which adversely affects the accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 11 publications
(11 reference statements)
2
20
0
Order By: Relevance
“…However, it is very difficult to precisely measure the shapes of micro-holes that have large length/diameter (L/D) ratios because of the difficulties encountered during probe fabrication and the complexities involved in employing a sensing method that uses a small measuring force. Many studies have been reported on micro-hole measurement techniques employing a variety of probes such as optical probes [1][2][3], vibroscanning probes [4,5], vibrating probes [6][7][8][9][10][11][12], tunneling effect probes [12,13], opto-tactile probes [14], fiber probes [15,16], optical trapping probes [17], and diaphragm or flexure based probes using an elastic mechanism [18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is very difficult to precisely measure the shapes of micro-holes that have large length/diameter (L/D) ratios because of the difficulties encountered during probe fabrication and the complexities involved in employing a sensing method that uses a small measuring force. Many studies have been reported on micro-hole measurement techniques employing a variety of probes such as optical probes [1][2][3], vibroscanning probes [4,5], vibrating probes [6][7][8][9][10][11][12], tunneling effect probes [12,13], opto-tactile probes [14], fiber probes [15,16], optical trapping probes [17], and diaphragm or flexure based probes using an elastic mechanism [18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Their latest development includes fiber Bragg grating sensors to measure the deflection of the three arc-shaped cantilevers holding the stylus [19]. The University of Kitakyushu is working on a vibrating fiber probing system [20]. It consists of an extremely fine optical fiber with a glass tip diameter of 5 µm, but it is limited to probing in x/y-direction only.…”
Section: Introductionmentioning
confidence: 99%
“…Various micro-CMM probes have also been developed [4,11,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Most of them are mechanical tactile probes working in the contact mode [4,11,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the contact mode microprobes usually apply styli with a limited aspect ratio to achieve a better measurement stability. To mitigate these problems, non-contact mode micro-CMM probes have been developed [21][22][23]. In the non-contact measurement mode, the probes are vibrated and the change of the vibration amplitude due to the probe sample's interaction is usually applied for measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation